Love's enlightenment rethinking charity in modernity - Hanley, Ryan Patrick 1974- (Cambridge University Press, 2017)
A number of prominent moral philosophers and political theorists have recently called for a recovery of love. But what do we mean when we speak of love today? Love's Enlightenment examines four key conceptions of other-directedness that transformed the meaning of love and helped to shape the way we understand love today: Hume's theory of humanity, Rousseau's theory of pity, Smith's theory of sympathy, and Kant's theory of love. It argues that these four Enlightenment theories are united by a shared effort to develop a moral psychology that can provide both justificatory and motivational grounds for concern for others in the absence of recourse to theological or transcendental categories. In this sense, each theory represents an effort to redefine the love of others that used to be known as caritas or agape - a redefinition that came with benefits and costs that have yet to be fully appreciated